Agricultural change in southern Derbyshire, 1770 to 1870, with special reference to the dairy industry - Dalton, Roger (1995)
The aim of this thesis is to investigate spatial and temporal aspects of agricultural change in southern Derbyshire between 1770 and 1870. During this period it is argued that the progress of dairying showed strong continuity with the developments of preceding centuries and experienced growth ahead of the reorientation towards liquid milk production in the latter nineteenth century. Contemporary and modern sources have been consulted, important among which are sale advertisements and other agricultural reportage published in the Derby Mercury newspaper. A significant outcome has been the elaboration of the prime role of dairying and the production of farmhouse cheese in the southern Derbyshire farm system with cattle and pig fattening, sheep rearing and grain production as subsidiary enterprises. Dairying was most intensively developed on heavier land: marls of the Mercian Mudstone, shales of the Westphalian and glacial till sheets but less so to the south of the Trent where soil conditions are more varied. Between 1770 and 1870 dairy production increased substantially as the proportion of land in arable declined. Contributory factors discussed include farm enlargement, higher stock rates and improved cattle breed. Of particular note was the feeding of brewers' grains from Burton. It is argued that as a consequence pastures may have been sustained above the common low level of management characteristic of the times.